2011
DOI: 10.1172/jci43157
|View full text |Cite
|
Sign up to set email alerts
|

Repeated TLR9 stimulation results in macrophage activation syndrome–like disease in mice

Abstract: Hemophagocytic lymphohistiocytosis (HLH) and macrophage activation syndrome (MAS) are 2 similar diseases characterized by a cytokine storm, overwhelming inflammation, multiorgan dysfunction, and death. Animal models of HLH suggest that disease is driven by IFN-γ produced by CD8 + lymphocytes stimulated by persistent antigen exposure. In these models and patients with "primary" HLH, the antigen persists due to genetic defects, resulting in ineffective cytotoxic responses by CD8 + T cells and poor pathogen clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
390
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 348 publications
(404 citation statements)
references
References 48 publications
14
390
0
Order By: Relevance
“…Recently, a new murine model of MAS induced by repeated stimulation of Toll-like receptor (TLR) 9 may provide some insight. 52 The rationale for this model involves multiple observations. Gene signatures consistent with chronic TLR/IL-1b signaling are present in sJIA patients.…”
Section: Proposed Pathophysiology Of Mas In Children With Sjiamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new murine model of MAS induced by repeated stimulation of Toll-like receptor (TLR) 9 may provide some insight. 52 The rationale for this model involves multiple observations. Gene signatures consistent with chronic TLR/IL-1b signaling are present in sJIA patients.…”
Section: Proposed Pathophysiology Of Mas In Children With Sjiamentioning
confidence: 99%
“…68 Whether the IFNg responding macrophage becomes a hemophagocyte, or whether it induces another cell type to become a hemophagocyte is unclear. Furthermore, although the presence of hemophagocytosis is correlated with development of anemia 68 and worsened disease activity, 52 there is of yet no direct demonstration that hemophagocytes are directly pathogenic. In fact, some authors have found potentially anti-inflammatory/regulatory properties for hemophagocytes.…”
Section: Proposed Pathophysiology Of Mas In Children With Sjiamentioning
confidence: 99%
“…This accumulation of antigen results in overstimulation of the frustrated lymphocytes, copious release of cytokines (a cytokine storm), and the resulting multiorgan pathology 13 . Such situations may arise when cytotoxic granule function is genetically intact as well 16 . Additionally, patients with systemic lupus erythematosus, systemic juvenile idiopathic arthritis, and 13 .…”
Section: Pathophysiology Of Hemophagocytic Syndromesmentioning
confidence: 99%
“…For instance, in mice, excessive Toll-like receptor 9 stimulation can lead to a perforin-independent -and indeed lymphocyte-independent -cytokine-driven HPS 16 . Given the clinical overlap between many features of VHF and rHPS, it is intriguing to speculate whether similar pathophysiology is at play at least in part in VHF.…”
Section: Pathophysiology Of Hemophagocytic Syndromesmentioning
confidence: 99%
See 1 more Smart Citation